INDONESIAN EFL TEACHERS TEACHING READING TO ENGLISH YOUNG LEARNERS IN INDONESIA AND THAILAND - Hidayatulloh, Sibakhul Milad Malik; Sugirin, Sugirin (LLT Journal: A Journal on Language and Language Teaching, 2022)
Among myriad research on teaching reading on English Young Learners, little has been discussed the practice within two different socio-culture settings. Indeed, the success stories of teaching reading to young learners with different social and cultural circumstances will be able to offer insight and new perspectives of teaching reading to EYL for researchers, mainly English teachers. This study aimed at narrating and exploring the process of teaching reading within two different countries, Indonesia and Thailand. This study invited two Indonesians EFL teachers who teach English to young learners in Indonesia and Thailand. Underpinning the narrative research design, this study narrated the experience of the participants from interview process triangulated by their narrative framework and teaching reading materials. From the obtained data, the findings were presented using four major themes: teaching experience, the students, teaching reading, and teaching reading materials. The result revealed that the participants had some similarities and distinction aspects. Teaching technique that the participants used could be said as the similar aspect of the participants. Meanwhile, teaching materials could be said as the integral factors underlaying the differences. Furthermore, organizational system and community around participants played significant role in affecting the differences and similarities.